A weakly pathogenic Rauscher spleen focus-forming virus mutant that lacks the carboxyl-terminal membrane anchor of its envelope glycoprotein. - Machida, C A (1985)
A mutant Rauscher spleen focus-forming virus (mutant 4-3) that causes mild splenic erythroblastosis in mice has a 44-base-pair deletion in the 3' region of its envelope glycoprotein (env) gene. The encoded glycoprotein terminates prematurely, lacks a hydrophobic membrane anchor, and has a shortened intracellular lifespan. An active site for causing erythroblast proliferation may occur in the undamaged amino-terminal domain of the env glycoprotein.